Pengaruh Budaya Organisasi dan Motivasi terhadap Kinerja Karyawan PT Amarta Zwara Guna (Inbound Id) Jakarta - dodi yudiardi (Fakultas Ekonomi Universitas Garut, 2016)
The purpose of this study was to determine the influence of organizational culture and motivation on the performance of employees of PT. Amarta Zwara Guna (Inbound Id) Jakarta. The method used by the writer is descriptive method, the data collection technique used by the writer is field research and library research. The data processing techniques used by the author are validity, reliability, and multiple regression analysis techniques using the Statistical Package for Social Science (SPSS) 20 computer program. Based on the results of research and discussion, it is known that organizational culture affects employee performance and motivation affects performance. The next employee for simultaneous testing showed that organizational culture and motivation had an effect on the performance of the employees of PT. Amarta Zwara Guna (Inbound Id) Jakarta.